A study on the influence of media use on college students' environmental protection behaviors - Yinhua, Hao; Yasin, Megat Al Imran; Ng, Boon Sim (Emerald Group Publishing, 2022)
Purpose: The purpose of this study is to explore the influence of media use on environmental protection behaviors among college students. Design/methodology/approach: A total of 182 college students from H universities, including science, engineering, liberal arts and art, were surveyed. This study used structural equation modeling (SEM) to analyze the data based on the proposed model, including media use, environmental protection awareness, environmental protection intentions and environmental protection behaviors, and then analyzed the impact of different gender, grade and disciplines on college students' environmental protection behavior by T-test and ANOVA. Findings: First, it can be seen from the structural equation model analysis that media use has a significant impact on environmental protection awareness and environmental protection intention of college students, while media use has no significant direct impact on their environmental protection behaviors, but environmental protection intention has a mediating effect between media use and environmental protection behaviors. Second, the analysis of control variables explained that gender and disciplines have no significant impact on college students' environmental protection behaviors, while grades do. Originality/value: Research on media use on environmental protection behavior was limited. This study proposed a new model of the impact of media use on environmental protection behavior and deeply analyzed the effect of media use from the perspective of environmental protection behavior. In addition, this study put forward research suggestions from the perspective of media publicity and environmental protection, hoping that the research conclusions could provide a basis and reference for ecological environment construction.